Protective Effect of Rosavin Against Intestinal Epithelial Injury in Colitis Mice and Intestinal Organoids - Luo H; Guo M; Li M; Zhao Y; Shen J; Du F; Chen Y; Deng S; Sun Y; Gu L; Li W; Li X; et al. (Dove Medical Press, 2024)
Haoming Luo,1,2,* Miao Guo,3,4,* Mingxing Li,1 Yueshui Zhao,1 Jing Shen,1 Fukuan Du,1 Yu Chen,1 Shuai Deng,1 Yuhong Sun,1 Li Gu,1 Wanping Li,1 Xiaobing Li,1 Meijuan Chen,1 Zhangang Xiao,1,5,6 Shengpeng Wang,3,4 Xu Wu1,7 1Cell Therapy & Cell Drugs of Luzhou Key Laboratory, Department of Pharmacology, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan, 646100, People's Republic of China; 2Department of Pharmacy, Three Gorges University Hospital of Traditional Chinese Medicine & Yichang Hospital of Traditional Chinese Medicine, Yichang, Hubei, 443003, People's Republic of China; 3State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People's Republic of China; 4Macao Centre for Research and Development in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People's Republic of China; 5Department of Pharmacy, Gulin County Hospital of Traditional Chinese Medicine, Luzhou, Sichuan, 646500, People's Republic of China; 6School of Pharmacy, Sichuan College of Traditional Chinese Medicine, Mianyang, Sichuan, 621000, People's Republic of China; 7Department of Paediatric Care, Luzhou People's Hospital, Luzhou, Sichuan, 646000, People's Republic of China*These authors contributed equally to this workCorrespondence: Shengpeng Wang, State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People's Republic of China, Email swang@um.edu.mo Xu Wu, Cell Therapy & Cell Drugs of Luzhou Key Laboratory, Department of Pharmacology, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan, 646100, People's Republic of China, Email wuxulz@swmu.edu.cnIntroduction: Rhodiola species have been utilized as functional foods in Asia and Europe for promoting health. Research has demonstrated that Rhodiola has the potential to alleviate inflammatory bowel disease (IBD) in animal models. However, the specific active components and the underlying mechanism for ameliorating intestinal damage remain unclear. This study aims to explore the relieving effect of Rosavin (Rov), a known active constituent of Rhodiola, in IBD and the regulatory mechanisms.Methods: The therapeutic effect of Rov was evaluated using a murine model of acute colitis induced by dextran sulfate sodium salt (DSS). Inflammatory cytokines and neutrophil activation markers were measured by corresponding kits. Immunohistochemistry, immunofluorescence, TUNEL, and EdU assays were applied to investigate the tight conjunction proteins expression, epithelial marker expression, number of apoptotic cells, and epithelial proliferation, respectively. The protection effect of Rov on gut epithelial injury was assessed using TNF-α-induced intestinal organoids. Additinally, RNA sequencing was applied to observe the genetic alteration profile in these intestinal organoids.Results: Oral administration of Rov significantly attenuated weight loss and restored colon length in mice. Notably, Rov treatment led to decreased levels of pro-inflammatory cytokines and neutrophil activation markers while increasing anti-inflammatory factors. Importantly, Rov restored intestinal despair by increasing the number of Lgr5+ stem cells, Lyz1+ Paneth cells and Muc2+ goblet cells in intestines of colitis mice, displaying reduced epithelial apoptosis and recovered barrier function. In TNF-α-induced intestinal organoids, Rov facilitated epithelial cell differentiation and protected against TNF-α-induced damage. RNA sequencing revealed upregulation in the gene expression associated with epithelial cells (including Lgr5+, Lyz1+ and Muc2+ cells) proliferation and defensin secretion, unveiling the protective mechanisms of Rov on the intestinal epithelial barrier.Discussion: Rov holds potential as a natural prophylactic agent against IBD, with its protective action on the intestinal epithelium being crucial for its therapeutic efficacy. Keywords: rosavin, colitis, inflammatory bowel disease, organoid, intestinal stem cell